Case reportBehçet disease – case report and review - Romańska-Gocka, Krystyna; Gocki, Jacek; Placek, Waldemar; Uchańska, Grażyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
We report a rare case of Behçet’s disease in a Caucasian man. Behçet’s disease is a chronic recurrent generalized vasculitis whose manifestation seems to be dependent on genetic predisposition triggered by environmental factors. It occurs endemically in central and eastern Asia. Dermatological symptoms are most common, including recurrent oral and genital aphthous ulcers. Severe ocular inflammation can lead to permanent impairment of vision. The involvement of other organ systems can potentially lead to life-threatening complications. We discuss the course of the disease, the clinical symptoms, the diagnostic criteria and methods of treatment.